Mineral resources, economics and the environment - Kesler, Stephen E. (Cambridge University Press, 2015)
"Written for students and professionals, this revised textbook surveys the mineral industry from geological, environmental and economic perspectives. Thoroughly updated, the text includes a new chapter on technology industry metals as well as separate chapters on mineral economics and environmental geochemistry. Carefully designed figures simplify difficult concepts and show the location of important deposits and trade patterns, emphasising the true global nature of mineral resources. Featuring boxes highlighting special interest topics, the text equips students with the skills they need to contribute to the energy and mineral questions currently facing society, including issues regarding oil pipelines, nuclear power plants, water availability and new mining locations. Technical terms are highlighted when first used, and references are included to allow students to delve more deeply into areas of interest. Multiple choice and short answer questions are provided for instructors online at www.cambridge.org/kesler to complete the teaching package"-- Provided by publisher
Keywords: Mines and mineral resources.; Mineral industries.; Mines and mineral resources -- Environmental aspects.; elektronické knihy; electronic books